Growth rate and its variability in erect Antarctic bryozoans - Barnes, David K. A.; Webb, Karen E.; Linse, Katrin (Polar Biology, 2007)
Climate is altering rapidly in parts of the Arctic and Antarctic but we know little about how marine organisms are responding to, or might respond to such changes. Knowledge of within-taxon variability is the vital context (currently missing) to interpretation of environmental signals. We investigated growth in six species and three genera of erect Antarctic bryozoans, an ideal model taxon to investigate such response. Cellarinella margueritae, C. nodulata, C. rogickae, C. watersi, Melicerita obliqua and Stomhypselosaria watersi, extended 3.4, 5.2, 4.6, 4.1, 4.9 and 4.5 mm year(-1) and synthesised 24, 55, 45, 176, 34 and 46 mg CaCO3 year(-1), respectively. The maximum ages of these species ranged from 11 to 15 years except M. obliqua, which reached 32 years. This is the first investigation of growth rates of closely related Antarctic invertebrate species and reports the slowest growth rates of bryozoans known from anywhere to date. Our data coupled with that from literature shows that Antarctic bryozoan growth varies << 10(1) between species, 10(1) between genera, 10(2) between morphologies and is similar to 10(1) slower than in tropical or temperate regions. However, within encrusting types the slowest growing species grow at similar rates from poles to tropics. Age was a strong confounding factor across our Antarctic study species but age-standardised data showed a possible decline in annual growth from 1992 to 2003. We identify several factors increasing this environmental signal strength, including (1) the importance of generic (though not necessarily species) identification and (2) use of dry-mass or ash-free dry-mass as the measures of growth.
Keywords: Sørishavet; bryozoa; klimaendringer; marin biologi; mosdyr

Antarctic Bryozoa - Vigeland, Immanuel (Dybwad, 1952)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq., instituted and financed by consul Lars Christensen
Keywords: Antarktis; bløtdyr; bryozoa; ekspedisjoner; forskning; mosdyr; zoologi